Economics of Adaptation to Climate Change : Mozambique, Volume 2. Annexes - World Bank (Washington, DC, 2013)
This report is part of a broader global study, the Economics of Adaptation to Climate Change (EACC), which has two principal objectives: (a) to develop a global estimate of adaptation costs for informing international climate negotiations; and (b) to help decision makers in developing countries assess the risks posed by climate change and design national strategies for adapting to it. The purpose of this study is to assist the Government of Mozambique in its efforts to understand the potential economic impacts of climate change and to support its efforts to develop sound policies and investments in response to these potential impacts. The Mozambique Economics of Adaptation to Climate Change (EACC) study selected four sectors that are believed to be vulnerable to climate change: (1) agriculture, which employs over 70 percent of the population; (2) energy, particularly hydropower generation, which is dependent on water runoff; (3) transport infrastructure, notably roads; and (4) coastal areas, which do not conform to a "sector" but characterize specific geographical areas vulnerable to floods and storm surges directly and indirectly related to sea level rise. The report ends with a discussion of seven lessons learned from the study. Volume 1contains the final report, and Volume 2 contains the Annexes,